Industrial pollution control and management in Ethiopia : a case study on Almeda textile factory and Sheba leather industry in Tigrai Regional State - Ghebretekle, Tsegai B. (2015)
As a new emerging industrializing nation, industrial pollution is a challenge in Ethiopia. To address the problem, the government has introduced different laws, policies, strategies and established environmental organizations at federal and regional levels. However, the government has not performed well in this regard due to various barriers militating against sustainable industrial pollution control and management. Partly this is due to organizational weaknesses, lack of effective implementation of standards as well as the absence of expertise and capacity building. The aim of this research is to investigate the practice of industrial pollution control and management in Ethiopia with particular emphasis on two selected industries. For the practical investigation a methodology that combines semi-structured interview from key informants in industrial pollution, together with documentary and observational data has been employed. The findings of the research show that the magnitude of industrial pollution is rapidly increasing in the country. This is particularly the case in the textile and leather industries. It is also more severe in urban centers where most of the industries are located. The problem is most operating industries in Ethiopia do not have waste treatment plants. They simply discharge their untreated effluent to the nearby rivers or drainage facilities in violation of the established standards. Even for those industries with treatment plants (including the two case study industries) the treatment plants are not functioning properly due to cost implications; and they discharge their effluent to the nearby rivers with nominal treatment. Thus, they are sources of damage to the environment and the nearby communities. The main barrier to industrial pollution control has been the application of weak form of sustainable development policy and lack of institutional regulations—including laws and organizational implementing mechanisms. This is manifested through lack of political will on the part of the government to enforce the existing industrial pollution control laws; lack of capacity (resource and personnel) and coordination among the environmental organizations. On the part of the affected community there is lack of awareness and organization to protect their constitutionally enshrined right—the right to clean and healthy environment. Similarly there is also lack of corporate social responsibility on the side of the two industries subject of the study.